Patrimônio cultural brasileiro na Constituição Federal de 1988 e a diversificação do instrumento do tombamento - Oliveira, Fábio André Uema (2018)
The present study intends to analyze the evolution of the legal concept of cultural heritage and the repercussion in the diversification of the use of its safeguard’s instrument, the tombamento. It analyzes the fundamentals of protection of cultural heritage, the institution of tombamento and the difficulties of applying this instrument since its emergence in the Brazilian legal system